6(2x-8)+3=14

Simple and best practice solution for 6(2x-8)+3=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-8)+3=14 equation:


Simplifying
6(2x + -8) + 3 = 14

Reorder the terms:
6(-8 + 2x) + 3 = 14
(-8 * 6 + 2x * 6) + 3 = 14
(-48 + 12x) + 3 = 14

Reorder the terms:
-48 + 3 + 12x = 14

Combine like terms: -48 + 3 = -45
-45 + 12x = 14

Solving
-45 + 12x = 14

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 12x = 14 + 45

Combine like terms: -45 + 45 = 0
0 + 12x = 14 + 45
12x = 14 + 45

Combine like terms: 14 + 45 = 59
12x = 59

Divide each side by '12'.
x = 4.916666667

Simplifying
x = 4.916666667

See similar equations:

| 9^3x*8^2x=1/36 | | 2/3=x/2+1/4 | | (q+4)(q-6)= | | 8x+5x=52 | | x-(2-x)=-2(2x-4) | | 9z^2-9z-9=0 | | y^2=y+12 | | n/6+48=62 | | 20+8x-5=8x+21 | | 8000+8000(.20-x)=7200 | | 59=7+4m | | 10x-5=25whatx | | -5x^2+450x-10000=0 | | -5x-3y=12 | | -10y+18=-15y-2+5y | | 5x+10-10=30 | | x^2-5xy+y^2=4 | | 3x-6=6x-36 | | 11x+16=6x+81 | | (2y+1)/4=(y-3)/3 | | (2y+1)/4=(y-3)/3 | | 4x/2x^2 | | 7k-(9k-16)=14-(19-k) | | x^2+xy=5 | | 8x-4=17+x | | ax-7a=1 | | 0.6-50y=3 | | x+3+8x=5x-12 | | (4x+2)/3+x/8=6 | | 1+ln(x)=0 | | 5x-22=-3x+2 | | n^2+1n-56=0 |

Equations solver categories